The Role of the International Criminal Court: A Literature Review on Its Effectiveness and Limitations - Begem, Sarah Sarmila (Asosiasi Ide Bahasa Kepri, 2024)
The International Criminal Court (ICC) plays a critical role in promoting global justice by addressing crimes against humanity, war crimes, and genocide. This literature review examines the effectiveness and limitations of the ICC in fulfilling its mandate. The study synthesizes findings from existing research to evaluate the court’s ability to prosecute offenders, deter future crimes, and support victims. Key factors influencing its effectiveness include jurisdictional constraints, the reliance on state cooperation, and the political dynamics within the United Nations Security Council. The review highlights significant achievements, such as landmark prosecutions and the establishment of legal precedents, while also identifying persistent challenges, including enforcement of arrest warrants and perceptions of bias. Furthermore, the study explores proposed reforms to strengthen the ICC's capacity to achieve its objectives. This review contributes to the discourse on international justice by providing a comprehensive analysis of the ICC's impact and areas for improvement, offering insights for policymakers, scholars, and practitioners in the field of international law.